Nitrogen evolution in the halo, thick disc, thin disc, and bulge of the Galaxy. Issue 1 (11th September 2021) - Grisoni, V; Matteucci, F; Romano, D
ABSTRACT: We study the evolution of nitrogen (N) in the Galactic halo, thick disc, thin disc, and bulge by comparing detailed chemical evolution models with recent observations. The models used in this work have already been constrained to explain the abundance patterns of α-elements and the metallicity distribution functions of halo, disc, and bulge stars; here, we adopt them to investigate the origin and evolution of N in the different Galactic components. First, we consider different sets of yields and study the importance of the various channels proposed for N production. Secondly, we apply the reference models to study the evolution of both the Galactic discs and bulge. We conclude that: i) primary N produced by rotating massive stars is required to reproduce the plateau in log(N/O) and [N/Fe] ratios at low metallicity, as well as the secondary and primary production from low- and intermediate-mass stars to reproduce the data of the thin disc; ii) the parallel model can provide a good explanation of the evolution of N abundance in the thick and thin discs, and we confirm that the thick disc has evolved much faster than the thin disc, in agreement with the results from the abundance patterns of other chemical elements; and iii) finally, we present new model predictions for N evolution in the Galactic bulge, and we show that the observations in bulge stars can be explained if massive stars rotate fast during the earliest phases of Galactic evolution, in agreement with findings from the abundance pattern of carbon.